PLASMABLASTIC LYMPHOMA. A STATE-OF-THE-ART REVIEW (1) - Michele Bibas (Mediterranean Journal of Hematology and Infectious Diseases)
The objective of this two-part study is to present current and comprehensive understanding on the diagnosis and management of plasmablastic lymphoma. The first section, as presented in this paper, is on the study of epidemiology, etiology, clinopathological characteristics, differential diagnosis, prognostic variables, and the impact of plasmablastic lymphoma on specific populations.